Loops in orthodontics- An extensive review (International Journal of Food and Nutritional Sciences, 2022)
Extraction therapies are commonly done in patients with protrusion and/or crowding which demands a thorough understanding of biomechanics. Two basic types of space closing mechanics are friction/sliding and frictionless/loop mechanics. In the former, the wire and position of the bracket are important factors in tooth movement but the simplicity of friction mechanics is offset by the binding between bracket and archwire and may be associated with undesirable side effects such as uncontrolled tipping and deep bite. In frictionless mechanics, specially designed springs are used which provides the required moment to force ratio (M/F ratio) in three dimensions and they are more predictable and versatile.